The role of perfectionism traits and affect in predicting academic dishnonesty of college students - Ali, Abdurosid Nur; Prasetyawati, Wuri (Humanitas: Indonesian Psychological Journal, 2025)
This study aimed to investigate the relationship between perfectionism traits and affect on academic dishonesty in college students. This study involved 98 students as participants who were voluntarily filling out the survey after the final exams. Data were collected using the academic dishonesty questionnaire, the multidimensional perfectionism scale, and the positive-negative affect scale. Data were analysed using a correlation and comparative approach. The study found that only the socially prescribed perfectionism domain positively correlated with academic dishonesty in college students. The effect of socially prescribed perfectionism was diminished by the presence of emotions while controlling several demographic variables as covariates. Positive affect shows a greater effect on reducing the possibility of academic dishonesty occurrence. It highlighted that perfectionism may not be directly associated with academic dishonesty and limitations of self-report as a measure of dishonesty in college students.